Nuevos Movimientos Eclesiales - Luís Miguel Figueiredo Rodrigues (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
The new ecclesial movements have a particular focus in recent times in the Church, and have come to be known as the Spring of the Spirit. This article addresses this reality, their characteristics and their potential. It highlights the pastoral opportunity to live and profess the apostolic faith in an ever more authentic way.